Desulfurization of Giral lignite of Rajasthan (Western India) using Burkholderia sp. GR 8–02. Issue 3 (4th March 2022) - Kumar, Aniruddha; Singh, Alok K; Singh, Prakash K; Singh, Asha Lata; Saikia, Binoy K; Kumar, Alok
ABSTRACT: Present investigation entails the results of desulfurization of high sulfur Giral (Rajasthan-India) lignite with the help of Burkholderia sp. GR 8–02. Total sulfur varies from 3.73% to 7.91%, where inorganic sulfur is 2.17–3.82%, pyritic and Sulfate sulfur is 0.90–2.42% and 0.47–2.84%, respectively. Chemical analysis, Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), scanning electron microscopy (SEM/EDS) were used in order to understand desulfurization. Bacterial treatment caused a significant reduction in total sulfur content ranging from 23.59% to 37.55%. Organic sulfur removal ranges from 11.06% to 20.54% while pyritic and Sulfate sulfur removal vary from 10.40–43.39% and 50.89–96.97%, respectively. In addition to desulfurization of lignite, the reduction in the ash yield and the volatile matter was also observed whereas there was a relative increase in the fixed carbon and elemental carbon content. Further, an increase in the gross calorific value from 3189 kcal/kg to 3482 kcal/kg was noticed.